OPTIMIZING SPORTS PERFORMANCE THROUGH MENTAL TOUGHNESS: PILOT STUDY - Răzvan KALININ; Robert BALAZSI; Iacob HANŢIU (Studia Universitatis Babeş-Bolyai: Educatio Artis Gymnasticae, 2020)
Background. Mental toughness is one of the most important and well-known psychological constructs in sports and beyond. Researchers in the field, argue that the development of mental toughness is based on both the influences of the environment in which the person operates and the learning and training processes that it went through them. “Gold Medal - Metal Training” it’s a program for developing mental toughness and it’s based on the work of several psychologists and coaches from Eastern Europe and Scandinavia. Aims. The aim of the present study was to verify the 4 essential aspects (process, resources, management and scientific) of the intervention program. Methods. The sample of this study consisted of N = 16 participants (31.8% male and 68.8% female), from a diverse range of sports (Judo, Hockey, Basketball, Triathlon, Dance, Athletics). Of these, 8 are performance athletes, and 8 are amateurs. Their age ranged from 19 to 44 years with a mean of M = 25.81 (SD = 7.70). Self-reports were obtained from all athletes regarding their mental toughness (Mental toughness Inventory) and the feasibility of the intervention program through a questionnaire in accordance with the objectives of the study. Results. Regarding the difference between statistical test indicate significant difference for item 2, item 3 and item 9. For the difference between the level of physical activity statistical test indicate significant difference for item 2. The results obtained in the ANOVA analysis with repeated measurements F (1, 15) = 8.257 (p = 0.012, MSE = 5.181, η² = 0.355) the F test is statistically significant despite the small sample size because the value of Eta (η²) far exceeds the threshold (> 0.14) in terms of a large effect. Conclusions. According to the results, the study is feasible with slight changes related to the implementation and organization of the process, so the coordinator must be more active in collaborating with subjects and provide them with information and suggestions more often.